Predisposing Factors for Pseudoplacentational Endometrial Hyperplasia or Cystic Endometrial Hyperplasia in Dogs and Their Association with Pyometra - Clarissa Helena Santana; Monique Ferreira Souza; Laice Alves da Silva; Lucas dos Reis de Souza; André Marcos Santana; Ayisa Rodrigues Oliveira; Tatiane Alves da Paixão; Renato Lima Santos (Veterinary Sciences)
Pseudoplacentational endometrial hyperplasia (PEH) and cystic endometrial hyperplasia (CEH) are both hyperplastic conditions that may occur in the canine uterus during diestrus. CEH can impair fertility, and, although the consequences of PEH are poorly known, this condition is significantly associated with pyometra. The aim of this study was to investigate frequencies of both PEH and CEH in female dogs according to age, size, breed, and breed group. Uteri from 300 female dogs were sampled and processed for histopathologic analyses. Lesions were identified, and frequencies were statistically compared. PEH was significantly more frequent in dogs between 4 and 12 years of age and significantly less frequent in Yorkshires than Shih-tzus, as well as in the breed group that includes Brazilian Terriers and Yorkshires. CEH was significantly more frequent in dogs older than 12 years, but no breed predisposition was observed. The frequency of PEH was significantly higher than that of CEH. The frequency of pyometra in PEH cases was significantly higher than endometritis or uterus without inflammation. This study identified age, breed group, and size as predisposing factors for PEH and further demonstrated the association between this condition and pyometra in dogs.